2011
DOI: 10.1039/c0cc04564k
|View full text |Cite
|
Sign up to set email alerts
|

Gold catalyzes the Sonogashira coupling reaction without the requirement of palladium impurities

Abstract: By a combination of kinetic and theoretical studies it is concluded that gold is intrinsically active to perform the Sonogashira coupling reaction between phenylacetylene and iodobenzene. The presence of Pd impurities is not mandatory for catalyst activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
107
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(118 citation statements)
references
References 12 publications
9
107
0
2
Order By: Relevance
“…[7] Recently it has been suggested that gold nanoparticles formed during the reaction could act as heterogeneous catalysts in these transformations. [8] An alternative approach to access Au I /Au III catalytic cycles under homogeneous conditions is to use a sacrificial external oxidant to perform the key oxidation of gold(I) to goldA C H T U N G T R E N N U N G (III). [9] A general mechanism for such processes is shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Recently it has been suggested that gold nanoparticles formed during the reaction could act as heterogeneous catalysts in these transformations. [8] An alternative approach to access Au I /Au III catalytic cycles under homogeneous conditions is to use a sacrificial external oxidant to perform the key oxidation of gold(I) to goldA C H T U N G T R E N N U N G (III). [9] A general mechanism for such processes is shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of DFT calculation, Corma and coworkers have also proposed that a similar type of oxidative addition process occurs during the reaction of iodobenzene with Au 38 . 15 In summary, we have demonstrated anomalous behavior of bimetallic Au/Pd alloy systems in the coupling reaction of PhB(OH) 2 with CBA at room temperature under aqueous conditions. The most important finding is that the reaction mechanism is likely to be completely different from that of the conventional SuzukiMiyaura coupling, which can be described in terms of the participation of a single metal (Pd).…”
mentioning
confidence: 99%
“…[24] Importantly, control reactions [25] indicated the need for both the acid and the oxidant, as well as a gold precatalyst; the failure of palladium, and various other late transition metals, to catalyse the transformation provided evidence against low-level impurities being responsible for the catalytic activity ascribed to gold. [26] Subsequent reaction optimisation [25] revealed that both Au I and Au III species-as well-defined complexes, simple salts or in combination with Ag I salts-were able to act as precatalysts for the IBA/p-TSA-mediated oxyarylation ( Table 2, entries 1-12). As with our previously reported methodology, [9] the reaction was sensitive to the steric and electronic environment about the gold centre: [AuClA C H T U N G T R E N N U N G (PPh 3 )] proved a more efficient precatalyst than complexes of bulky and/or strong donor ligands (entry 1 vs. entries 6-10).…”
Section: Resultsmentioning
confidence: 99%